2000
DOI: 10.1111/j.1475-2743.2000.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen losses from outdoor pig farming systems

Abstract: Abstract. Nitrogen losses via nitrate leaching, ammonia volatilization and nitrous oxide emissions were measured from contrasting outdoor pig farming systems in a two year field study. Four 1-ha paddocks representing three outdoor pig management systems and an arable control were established on a sandy loam soil in Berkshire, UK. The pig management systems represented: (i) current commercial practice (CCP) -25 dry sows ha 71 on arable stubble; (ii)`improved' management practice (IMP) -18 dry sows ha 71 on stub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…Williams et al (2000) showed that nitrate leaching can be greatly reduced by using a management system that stocks pigs on established grassland compared to arable stubbles. After 6-month stocking, the vegetative cover on the grass system had been destroyed so in the following winter nitrate losses were similar from both systems.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (2000) showed that nitrate leaching can be greatly reduced by using a management system that stocks pigs on established grassland compared to arable stubbles. After 6-month stocking, the vegetative cover on the grass system had been destroyed so in the following winter nitrate losses were similar from both systems.…”
Section: Introductionmentioning
confidence: 99%
“…I n response to consumers'demand for`naturally' raised pigs, an increasing number of breeding sows is being kept outdoors in Europe, especially in the UK, France and Denmark (Mortensen et al 1994;Denmat et al 1995;Watson & Edwards 1997). Outdoor pig production has benefits in terms of animal welfare and low costs of buildings and equipment (Deering & Shepherd 1985), but it may have hidden costs due to losses of nutrients to aquifers used for public water supply (Worthington & Danks 1992) or to the atmosphere (Petersen et al 1999;Sommer & MÖller 1999;Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands are the most important sources of N 2 O emissions in temperate systems, and the effects of grassland management on N 2 O emissions have been extensively reported (Merino et al, 2005;Dobbie & Smith, 2006;Jones et al, 2006;Ball et al, 2007). The large amounts of N input received by grasslands, together with the excreta returned by grazing animals and thus concentrated in small areas have been identified as particularly important causes of high rates of N 2 O emissions Williams et al, 2000). This heterogeneity makes an assessment of emissions from grazed areas with the conventional cover box measurements particularly challenging.…”
Section: Soiluse and Managementmentioning
confidence: 99%
“…The large amounts of N input received by grasslands, together with the excreta returned by grazing animals and thus concentrated in small areas have been identified as particularly important causes of high rates of N 2 O emissions (Oenema et al. , 1997; Williams et al. , 2000).…”
mentioning
confidence: 99%